2018
DOI: 10.1155/2018/7048078
|View full text |Cite
|
Sign up to set email alerts
|

Body Mass Index at Pediatric Leukemia Diagnosis and the Risks of Relapse and Mortality: Findings from a Single Institution and Meta-analysis

Abstract: High body mass index (BMI) is associated with relapse of certain adult cancers, but limited knowledge exists on its association with pediatric leukemia relapse. We evaluated the association between overweight/obesity (BMI ≥ 85th percentile) at pediatric leukemia diagnosis and relapse or mortality. A meta-analysis combining our findings with those of previous studies was also performed. The study included 181 pediatric leukemia patients. Sporadic missing data were multiply imputed, and hazard ratios (HR) and 95… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
19
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(20 citation statements)
references
References 43 publications
1
19
0
Order By: Relevance
“…Obesity may impact treatment outcomes in ALL. Overweight and obese children have worse event-free survival and a higher rate of morbidities than non-obese children during the induction phase [ 57 , 58 , 59 , 60 ]. Furthermore, obesity during the premaintenance chemotherapy phase is a risk factor for hypertension (OR 3.27; 95% CI 1.10–10.00; p = 0.05), hyperglycemia (OR 2.62; 95% CI 1.04–6.56; p = 0.04), and febrile neutropenia (incident rate ratio 1.53; 95% CI 1.10–2.12; p = 0.01) [ 60 ].…”
Section: Obesity In Childhood All Survivors and Its Effects On Outmentioning
confidence: 99%
“…Obesity may impact treatment outcomes in ALL. Overweight and obese children have worse event-free survival and a higher rate of morbidities than non-obese children during the induction phase [ 57 , 58 , 59 , 60 ]. Furthermore, obesity during the premaintenance chemotherapy phase is a risk factor for hypertension (OR 3.27; 95% CI 1.10–10.00; p = 0.05), hyperglycemia (OR 2.62; 95% CI 1.04–6.56; p = 0.04), and febrile neutropenia (incident rate ratio 1.53; 95% CI 1.10–2.12; p = 0.01) [ 60 ].…”
Section: Obesity In Childhood All Survivors and Its Effects On Outmentioning
confidence: 99%
“…Concerning ALL overweight/obese patients, the meta-analysis revealed an increased mortality and relapse risk (HR = 1.79, 95% CI = 1.03-3.10) and (HR = 1.28, 95% CI = 1.04-1.57) respectively. Similarly, an association between obesity and increased risk of mortality was observed for AML patients (HR = 1.64, 95% CI = 1.32-2.04) [63].…”
Section: Nutritional Status and Clinical Outcomementioning
confidence: 71%
“…In the recent retrospective analysis, Saenz et al [63] evaluated the association between overweight/obesity (BMI ≥ 85th percentile) at pediatric leukemia diagnosis and relapse or mortality. The study included 181 pediatric patients diagnosed with ALL, AML, and chronic myeloid leukemia (CML).…”
Section: Nutritional Status and Clinical Outcomementioning
confidence: 99%
“…The prevalence of obesity was higher than average for both survivors and siblings, although the survivors had higher obesity rates than their siblings (13.5% vs. 7.5%). Previous research has demonstrated that being overweight and obese is related to an increased risk of cancer recurrence and mortality for pediatric cancer survivors older than 10 years (Saenz et al, 2018). Hence, weight management via targeted counseling for physical activity and diet needs to be initiated as early as possible.…”
Section: Discussionmentioning
confidence: 99%